Diluted Seawater and Ammonia-N Tolerance of Two Mangrove Crab Species. New Insights to Understand the Vulnerability of Pristine Islands Ecosystems Organisms - Mégevand, Laura; Theuerkauff, Dimitri; L’Épine, Claire; Hermet, Sophie; Corse, Emmanuel; L’Honoré, Thibaut; Lignot, Jehan-Hervé; Sucré, Elliott (Frontiers in Ecology and Evolution, 2022)
Mangrove ecosystems are the primary receptors of anthropogenic pollution in tropical areas. Assessing the vulnerability of these ecosystems can be expressed, among other indicators, by studying the health of ‘ecosystem engineers’. In this study, mangrove forests facing opposing anthropogenic pressures were studied i) in the uninhabited island of Europa (Mozambique Channel), considered as a pristine ecosystem, and, ii) on the island of Mayotte, facing regular domestic wastewater discharges. Using an ecophysiological approach, the effects of diluted seawater (DSW) and increased ammonia-N were studied for two fiddler crab species: Gelasimus tetragonon (GT) on the island of Europa and Paraleptuca chlorotphthalmus (PC) on the island of Mayotte. Osmoregulation curves and osmoregulatory capacity were determined along with O2 consumption rates after a 96h exposure period. Histological analyses were also carried out on two important metabolic organs: the hepatopancreas and the posterior gills. Results indicate that both crab species are good hyper-hypo-osmoregulators but only PC can maintain its osmoregulatory capacity when exposed to ammonia-N. Oxygen consumption is increased in GT after 96h of exposure to ammonia-N but this does not occur in PC. Finally, a thickening of the gill osmoregulatory epithelium was observed after 96h in PC when exposed to ammonium but not in GT. Therefore, the two species do not have the same tolerance to DSW and increased ammonia-N. PC that is more exposed to chronic inputs of freshwater and effluents in its natural environment, develop physiological acclimation capacities in order to better manage nitrogenous enrichments. These results along with those from other studies regarding the effects of domestic effluents on mangrove crabs are discussed. Therefore, the greater vulnerability of organisms occupying pristine ecosystems could induce major changes in mangrove functioning if crabs, that are engineer species of the ecosystem, are about to reduce their bioturbation activity or, even, disappear from the mangrove forests.